Reinforcement Learning from AI Feedback A Review - Prof. (Dr) Satya Singh,; Ratnesh Kumar Sharma, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Reinforcement Learning from AI Feedback (RLAIF) is a big step forward compared to Reinforcement Learning from Human Feedback (RLHF). It's especially useful for large language models like GPT-4. RLAIF is better because it can handle more data at scale and is more efficient. It uses AI-generated feedback instead of human feedback. This shift to AI-generated feedback enhances the efficiency and speed of training AI systems. Additionally, RLAIF optimizes the AI's ability to align with desired outcomes, although it may not directly improve understanding human preferences. RLAIF uses a Preference Model (PM) that follows constitutional principles. This ensures that AI responses are ethical, safe, and high -quality. The constitution sets rules for AI decision-making. It makes sure AI follows ethical and social standards. This is important as AI keeps evolving. RLAIF is moving towards an automated, moral feedback system focusing on responsible AI governance and ethical guidelines.
Keywords: Reinforcement Learning; AI Generated Feedback; Machine Learning; Reward Signals; Interactive Learning